Protocadherins at the Crossroad of Signaling Pathways - Pancho, Anna; Aerts, Tania; Mitsogiannis, Manuela D.; Seuntjens, Eve (Frontiers in Molecular Neuroscience, 2020)
Protocadherins (Pcdhs) are cell adhesion molecules that belong to the cadherin superfamily, and are subdivided into clustered (cPcdhs) and non-clustered Pcdhs (ncPcdhs) in vertebrates. In this review, we summarize their discovery, expression mechanisms, and roles in neuronal development and cancer, thereby highlighting the context-dependent nature of their actions. We furthermore provide an extensive overview of current structural knowledge, and its implications concerning extracellular interactions between cPcdhs, ncPcdhs, and classical cadherins. Next, we survey the known molecular action mechanisms of Pcdhs, emphasizing the regulatory functions of proteolytic processing and domain shedding. In addition, we outline the importance of Pcdh intracellular domains in the regulation of downstream signaling cascades, and we describe putative Pcdh interactions with intracellular molecules including components of the WAVE complex, the Wnt pathway, and apoptotic cascades. Our overview combines molecular interaction data from different contexts, such as neural development and cancer. This comprehensive approach reveals potential common Pcdh signaling hubs, and points out future directions for research. Functional studies of such key factors within the context of neural development might yield innovative insights into the molecular etiology of Pcdh-related neurodevelopmental disorders.